Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/0020720920983504
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Research on the construction of university education information platform supported by cloud computing

Abstract: The level of information construction in Colleges and universities is an important indicator to reflect the level of education in Colleges and universities. With the development of cloud computing technology, how to solve the above problems and how to use cloud computing to improve the university education information platform is a problem that the builders of university education information platform should think deeply. This paper first analyzes the current situation of university education information cloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Indoria, P et al argue that cloud manufacturing is valuable according to the cloud platform manufacturing network, thereby enabling the sharing of manufacturing services and solutions, and also plays an important building role [18]. Jiang, J et al mainly studied the application of cloud computing technology on educational information in colleges and universities and concluded that the level of informatization construction in colleges and universities is an important indicator that affects the level of education in colleges and universities as well as the construction of culture [19].…”
Section: Related Workmentioning
confidence: 99%
“…Indoria, P et al argue that cloud manufacturing is valuable according to the cloud platform manufacturing network, thereby enabling the sharing of manufacturing services and solutions, and also plays an important building role [18]. Jiang, J et al mainly studied the application of cloud computing technology on educational information in colleges and universities and concluded that the level of informatization construction in colleges and universities is an important indicator that affects the level of education in colleges and universities as well as the construction of culture [19].…”
Section: Related Workmentioning
confidence: 99%
“…The current era emphasizes the importance of concentrating on exploring the objects, ways, and purposes of talent training, strengthening the leading role of the Party in educational work, doing a good job in establishing moral education, improving the strength of ideological education, and strengthening the strength of educational reform to make up for the shortcomings [1][2][3]. It is also necessary to add more Chinese characteristics to the educational work, to realize the development of education modernization, to improve the people's sense of honor and access, and to improve the role of influence in the world [4][5][6][7]. The most crucial link in the work of political education in colleges and universities is "establishing moral education", and the importance of political education should be strengthened in the whole process of education.…”
Section: Introductionmentioning
confidence: 99%